Analysis Of Fintech Payment Apps And Hedonistic Lifestyle On The Impulsive Buying Habits To UNPRI Students (Impact On Online Shopping Habits): Analisis Financial Technology dan Lifestyle Hedonis Terhadap Kebiasaan Impulsive Buying Mahasiswa UNPRI (Dampak Terhadap Kebiasaan Belanja Online) - Caroline Fransisca; Petrus Loo (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
Motivated by the growing adoption of financial technology and the rise of hedonistic lifestyles among students, this research aims to analyze the effect of financial technology and hedonistic lifestyles on the impulsive buying habits of students at Universitas Prima Indonesia (UNPRI) Medan. This study employs a quantitative approach using a Using a quantitative survey of 100 Management students of Universitas Prima Indonesia (UNPRI) Medan selected via incidental sampling, considering the characteristics of Generation Z, selected through incidental sampling techniques. The analysis results indicate that financial technology and hedonistic lifestyle have a positive and significant impact on impulsive buying. The R² value of 0.482 indicates that 48.2% % of the variance in impulsive buying is explained by these predictors, with effect sizes of 0.111 (fintech, weak) and 0.215 (hedonistic lifestyle, moderate). We recommend enhancing financial literacy programs and embedding budget‑reminder features in fintech apps to curb impulsive spending, while future research can examine moderators such as emotional intelligence and peer influence